Body mass and habitat correlates of song structure in a primitive group of birds - Bertelli, Sara Beatriz (2002)
We assessed relationships between acoustic frequency, body mass, and habitat in tinamous. This monophyletic group of primitive birds comprises 47 ground dwelling species whose habitats range from dense humid forest to open grasslands.The relationship between frequency and body mass was found to be negative, while the songs of open habitat species exhibited higher frequencies and a wider bandwidth than the closed-habitat ones. Residual variation in song frequency, after controlling for the effect of body mass and phylogeny, tends to differ among habitats. However, a statistical test of this pattern was not possible because of the existence of only five pairs of sister species differing in habitat. In spite of this, positive contrasts of bandwidth were associated with positive contrasts of habitat, confirming that songs of open-habitat species have a wider bandwidth than those of their more closed habitat relatives.